Study on high-speed electric motor cooling with oil spray - Xuehui Wang; Yuying Yan; Ying Li (e-Prime: Advances in Electrical Engineering, Electronics and Energy, 2023)
The transportation sector is experiencing quick electrification to pave the way to carbon-neutral society, which poses great challenges to the thermal management technologies for the motor as they are expected to be more and more powerful. Advanced cooling with oil spray on the end winding was reported experimentally and theoretically in this work. It was suggested that with the oil spray cooling, the temperature of winding was well within the safety range, indicating it is an efficient way to dissipate the heat for high-speed motors. Furthermore, a lumped-parameter model for motor was also introduced. It was found that the main heat transfer thermal resistance of winding is the resistance between the yoke and winding. Meanwhile, the main influencing parameters of spray system are heat transfer coefficient and wetting ratios of spray. The paper is expected to lay a solid foundation for the application of oil spray cooling in high-speed motor thermal management.